Eksperimentasi Pembelajaran Matematika Dengan Strategi Discovery Learning Terintegrasi learning Start With A Question (LSQ) Ditinjau Dari Komunikasi Matematis Pada Siswa Kelas VIII SMP Negeri 2 gatak - SUGIYARNO PUTRI, YURIDA (2016)
The aims of this research is to know the influence of the Discovery Learning strategy based on Learning Start With A Question strategy on mathematics achievement in terms of the communication of ability. This research is a experimental research to treat learning strategy. The population of this research is all student of class VIII SMP Negeri 2 Gatak of years 2014/2015 with 8 class. The sample of this research is determined by cluster random sampling technique, in order to obtain VIII F as the experimental class and VIII C as the control class. The instrument of this research used a mathematics communication ability questionnaire and mathematics achievement test. The collected data were analyzed using two way Anova before that do normalitas test use Liliefors method and homogenitas test use Bartlett method and then Sceffe test. The results showed that: (1) there is a different between strategi pembelajaan Discovery Learning terintegrasi Learning Start Wih A Question strategy in learning achievement, with FA = 9,672, (2) there is a different the communication level of ability in learning achievement of students, with FB = 9,778, (3) there is no interaction between pembelajaan Discovery Learning integrated Learning Start Wih A Question strategy of the mathematics communication of ability in mathematics achievement, with FAB = 0,112.